STUDY LITERATUR: QUERY EXPANSION PADA TEMU KEMBALI INFORMASI (INFORMATION RETRIEVAL) - Shalihah, Rifa'atus; Rifai, Sitti Najmia; Wiradarma, Arga; Nurfajrin. S, A. Ainun (Universitas Tabanan, 2025)
Information Retrieval plays a crucial role in assisting users in locating relevant documents within increasingly large data collections. One of the main challenges in the retrieval process is the mismatch between the terms used in a user’s query and the vocabulary contained in documents. Query expansion is widely employed to enrich the initial query by adding related terms, thereby broadening the representation of the user’s information needs. This article presents a literature review of several commonly used query expansion methods, including thesaurus-based approaches, WordNet, association rules, and relevance feedback. This review provides a comprehensive overview of the various query expansion techniques that have been developed within the field of Information Retrieval and serves as a reference for future research aimed at advancing more effective retrieval methods.